Glucocorticoid maintenance therapy and severe infectious complications in ANCA-associated vasculitis: a retrospective analysis - Speer, Claudius; Altenmüller-Walther, Christine; Splitthoff, Jan; Nußhag, Christian; Kälble, Florian; Reichel, Paula; Morath, Christian; Zeier, Martin; Bergner, Raoul; Schaier, Matthias (Rheumatology international, 2021)
To study the impact of glucocorticoid maintenance dose and treatment duration on outcomes in patients with AAV (ANCA-associated vasculitis) with emphasis on infectious complications. A total of 130 AAV patients from two German vasculitis centers diagnosed between August 2004 and January 2019 treated with cyclophosphamide and glucocorticoids for induction therapy and glucocorticoids for maintenance therapy were retrospectively enrolled. We investigated the influence of glucocorticoid maintenance therapy on patient survival, time to relapse, kidney function, infectious complications and irreversible physical damage. The patients were divided into the following groups: patients treated according to the predefined reduction scheme (< 7.5 mg) or patients treated with glucocorticoids ≥ 7.5 mg after 6 months. Compared to patients receiving < 7.5 mg glucocorticoids after 6 months, patients receiving $$\ge $$7.5 mg had an increased rate of infectious episodes per patient (1.7 vs. 0.6; p < 0.001), including urinary tract infection (p = 0.007), pneumonia (p = 0.003), opportunistic pneumonia (p = 0.022) and sepsis (p = 0.008). Especially pneumonia during the first 24 months after disease onset [hazard ratio, 3.0 (95% CI 1.5 − 6.1)] led to more deaths from infection (p = 0.034). Glucocorticoid maintenance therapy after 6 months had no impact on relapse rate or patient survival and decline in kidney function was comparable. Glucocorticoid maintenance therapy with $$\ge $$7.5 mg after 6 months is associated with more severe infectious complications leading to an increased frequency of deaths from infection. Glucocorticoid maintenance therapy has no effect on time to relapse or patient survival and should therefore be critically revised throughout the aftercare of AAV patients.
Published online: 22 November 2020
Gesehen am 18.10.2021